A study on trichosporon isolation, its molecular identification, clinical manifestations and risk factors - Azim, Wan Amani Wan Abdul (2018)
Trichosporon infection is a rare opportunistic, life threatening mycosis in patients with predisposing factors such as underlying immunodeficiency. Conventional methods to diagnose trichosporonosis are inadequate compared to molecular methods in terms of species identification. We reviewed 155 patients with Trichosporon isolations in hospital to study the proportion, clinical manifestations, outcome and risk factors for having Trichosporon infections. We found out that the majority species isolated were T. asahii (50.3%) and mostly were from urine samples (84.5%). Among risk factors for overall Trichosporon infections were ICU admission (95%CI 1.70, 10.37, p=0.002) and antifungal recipients (95%CI 0.06, 0.56, p=0.003). For Trichosporon fungemia, there were significant associations among those with hematological malignancy (p=0.001), antifungal recipients (p=0.002) and mortality (p=0.036). Mortality was observed more in fungemia compared to overall infection (55.6% vs. 22.5%). We also performed molecular identification on 39 available Trichosporon isolates (36 T. asahii, two T. mucoides and one T. inkin) by ITS1/4 sequencing that were previously identified by conventional method. We observed four discrepancies by conventional method where two T. asahii were identified as T. montevideense and two T. mucoides were T. debeurmannianum by ITS sequencing. In conclusion, Trichosporon infection in susceptible patients posed high mortality risk which required molecular identification for species identification to guide proper therapy.